Provose Workforce Competency Verification and Validation Process for Heavy Oil Operation to Achieve Zero Incident and Fatality - Supriatna, Cucu; Hidajat Tjakraatmadja, Jann (The Indonesian Journal of Business Administration, 2016)
Abstract. Heavy Oil Operational Unit (HOOU) is one of business unit in PT Chevron Pacific Indonesia, located in Duri Field Sumatra which well known for its Duri Steam Flood (DSF) project, The biggest Steam Flood Project in the World. HOOU has a strong commitment and fully aware to develop new operational culture in implementing Operational Excellent (OE) focuses on personal safety, process safety, and environment. Â Since 2012 IBU overall numbers Incidents have decreased significantly but in Heavy Oil Operation Unit (HOOU) those number remain unchanged significantly year over year, in 2015 Heavy Oil Operation recorded 6 cases of Day Away From Work (DAFW), 94 cases of Motor Vehicle Crash (MVC), and 5 cases of Oil Spill, it clearly much work remains ahead of us and there are a lot of challenges for doing some improvement in effort how to reduce those numbers of incidents. HOOU consists of several main Water and Oil Treating Facilities, hundreds of Steam Generators and thousands of Oil wells and Pump Unit scattered in around 13 Production areas. A large number of vehicles are another challenges, HOOU operates almost 2,000 vehicles both light and heavy vehicle with average miles driven per year reaches 17,485,006 miles/year. Safeguard is another critical issue to be addressed to ensure all safeguards are in place and functioning. Based on current condition as mentioned above HOOU need applying a new program to improve all workforce competencies in Motor Vehicle Safety (MVS) and Managing Safe Work through Verification and Validation Program (V&V) to achieve our objective â€œzero incidents and fatalitiesâ€. Â Keywords: Heavy Oil, Operational Excellent, Personal Safety, Process Safety, Motor Vehicle Safety, Managing Safe Work, Verification and Validation